2014
DOI: 10.1007/s10493-014-9861-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal climatic variations influence the efficacy of predatory mites used for control of western flower thrips in greenhouse ornamental crops

Abstract: This research investigated seasonal climate changes within greenhouses and the impacts they have on efficacy of the predatory mites Amblyseius swirskii and Neoseiulus cucumeris. Controlled environment chamber, greenhouse small-cage, and commercial greenhouse trials were conducted to determine which biological control agent is more efficacious for control of the pest western flower thrips (WFT), (Frankliniella occidentalis) on ornamental crops.When observed under laboratory conditions, predation and oviposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…In temperate climates, A. swirskii provides better thrips control than N. cucumeris in summer, whereas both predators show similar efficacy in winter. In growth chamber trials, predation and oviposition rates of both predator species showed no major differences between simulated summer and winter greenhouse conditions, so the difference in performance in summer is likely related to better survival of A. swirskii (Hewitt et al 2015). However, as N. cucumeris is significantly less expensive than A. swirskii, this predator might be the better option in winter (Hewitt et al 2015).…”
Section: Environmental Factorsmentioning
confidence: 90%
See 1 more Smart Citation
“…In temperate climates, A. swirskii provides better thrips control than N. cucumeris in summer, whereas both predators show similar efficacy in winter. In growth chamber trials, predation and oviposition rates of both predator species showed no major differences between simulated summer and winter greenhouse conditions, so the difference in performance in summer is likely related to better survival of A. swirskii (Hewitt et al 2015). However, as N. cucumeris is significantly less expensive than A. swirskii, this predator might be the better option in winter (Hewitt et al 2015).…”
Section: Environmental Factorsmentioning
confidence: 90%
“…In growth chamber trials, predation and oviposition rates of both predator species showed no major differences between simulated summer and winter greenhouse conditions, so the difference in performance in summer is likely related to better survival of A. swirskii (Hewitt et al 2015). However, as N. cucumeris is significantly less expensive than A. swirskii, this predator might be the better option in winter (Hewitt et al 2015). Unfortunately, similar comparative greenhouse studies between A. swirskii and other recently commercialized phytoseiid predatory mites (e.g., A. limonicus and T. montdorensis) have not yet been done.…”
Section: Environmental Factorsmentioning
confidence: 90%
“…cucumeris , A. swirskii proved to be a better WFT predator than in sweet pepper, as females showed a higher propensity to attack and kill WFT larvae . In chrysanthemum, A. swirskii provided higher thrips control than N. cucumeris in summer, likely owing to a better survival, while both predators showed similar efficacy in winter . Efficiency of A. swirskii as a WFT biocontrol agent is also influenced by host plant species, and here increased trichome densities hinder mite performance .…”
Section: Wft Control Tacticsmentioning
confidence: 97%
“…However, until recently, studies focusing on the reproductive biology or predatory activity of predatory mites had considered the influence of light intensity (quality) or day length (quantity, photoperiod) under simulated conditions in a particular season (Smith & Newsom, 1970;Maeda et al, 2000;Kazak et al, 2004;Zilahi-Balogh et al, 2007). Only recently has the effect of seasonal climatic variations on the efficacy of predatory mites for thrips control in greenhouses been addressed (Hewitt et al, 2015). Our study shows that the behavioral pattern of predation changed daily and seasonally, although photoperiod and temperature in the rearing chambers remained the same during the whole experimental period, and these changes were species-specific.…”
Section: Discussionmentioning
confidence: 99%